Analisis Pengaruh Struktur Modal Terhadap Praktik Manajemen Laba - ines devina; Sandy Harianto; Johan Yanto (Universitas Prasetiya Mulya, 2019)
The research objective is to analyze the influence of capital structure on earnings management practices. The research using multiple regressions examined 192 non-financial companies listed on Indonesia Stock Exchange from 2005 to 2014 period. The proxies of capital structure are debt-to-equity ratio and debt-to-asset ratio, while earnings management calculated through discretionary accruals from Jones, Modified Jones, cross-sectional industrial models. The results showed that there is a negative significant influence from firm’s capital structure to earnings management (α <0.05). This indicates that higher use of debt would increase the difficulties of debt covenant performance requirements; hence it increases the degree of control over the company, leaving less opportunity for earnings management.